Project based learning based on aesthetic science activities :a creative solution to reduce students' science learning anxiety - Pratama, Dear Budi; Fadly, Wirawan (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study examines the effect of project-based learning model based on aesthetic science activities on reducing science learning anxiety in students. The study used a quasi-experimental design involving 58 students who were divided into experimental and control groups. Data were collected through pretest and posttest questionnaires of science learning anxiety, as well as interviews with parents, teachers, and students to find out the main motives experienced by students after the intervention was carried out on science learning anxiety. The experimental group using the project-based learning model based on aesthetic science activities showed a significant decrease in learning anxiety compared to the control group using conventional learning methods. This model encourages students to engage in practicum-based projects and collaborative learning that enhances creativity, problem-solving skills and self-confidence. The ancova test results showed a significance value of 0.210 > 0.05, indicating the effectiveness of this learning model in creating a supportive and interactive learning environment. This research confirms that this approach is effective in reducing science learning anxiety and increasing students' interest and positive attitude towards science.